Efektivitas Proses Mediasi Perkara Waris Di Pengadilan Agama Blitar (Studi Kasus Nomor Perkara 1106/Pdt.G/2024/PA.BL) - AZIZAH, PUTRI NAYLA FADLILATUL; wafie, slamet (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2025)
Mediation is a dispute resolution process in which the parties involved try to reach an agreement with the help of a neutral and impartial mediator. This research discusses the effectiveness of the mediation process in inheritance cases at the Blitar Religious Court. This research aims to assess the extent to which mediation can function as an alternative dispute resolution, especially civil inheritance cases. This research uses qualitative methods and data collection uses observation, interviews and documentation or library research. The research results show that the mediation process at the Blitar Religious Court was able to resolve the settlement effectively and reach an agreement between the parties. However, this research also revealed several obstacles, such as resistance from certain parties and many parties who do not fully understand the benefits and mechanisms of mediation. They may consider litigation as the only way to resolve disputes, so they tend to be reluctant to try alternative approaches such as mediation. Overall, this research emphasizes the importance of mediation as an effective method of resolving legal conflicts, as well as transforming the capacity of mediators and increasing public awareness of the benefits. mediation in resolving disputes, especially civil cases. And in this case study, mediation was successfully carried out by reconciling the inheritance case with case number 1106/Pdt.G/2024/PA.BL